Discrete multi-target linear-quadratic control problem and quadratic programming - K. Khunsmuth (2018)
We consider a discrete multi-target linear-quadratic control problem. We reduce the problem into a quadratic programming over a simplex. Computing the coefficients of the cost function requires knowing the descriptions of the orthogonal project onto the vector space Z and the orthogonal complement Z ⊥ of the vector space Z. © 2013 K. Khunsmuth and T. Mouktonglang.